PELAKSANAAN MUSYAWARAH PERENCANAAN PEMBANGUNAN DESA DI DESA UJUNG MATTAJANG KECAMATAN MAPPEDECENG KABUPATEN LUWU UTARA - Muhammad Riyan Pratama; Fatmawati Fatmawati; Ruskin Azikin (Department of Public Administration, Muhammadiyah University of Makassar, 2018)
This researchconcerns on the implementation of conference of village devolvement planning in Ujung Matajang village, Mappedeceng district, North Luwu regency. The objective of this research is know the implementation of conference of village devolvement planning in Ujung Matajang village, Mappedeceng district, North Luwu regency and To find out the obstructive factor in that planning.This research is descriptive-qualitative type.The collection data technique applied were observation, interview, and documentation. The number of informants in this research is eleven people. The result of this research reveals that the implementation of conference of village devolvement planning in Ujung Matajang village, Mappedeceng district, North Luwu regency is running well. It can be proved on two indicators, planning stage and implementation stage. Keyword: conference, planning, village development